University students’ condom use during the COVID-19 pandemic: Cross-cultural differences and what predict them - Dacosta, L.; Morandini, J. S.; Pinkus, R. T.; De Caluwé, E.; Chan, L. S.; Lo, O.; Thongnopakun, S.; Visanuyothin, S.; Harasymchuk, C.; Joel, S.; Dale, V.; Rodrigues, D. L.; et al. (Journal of Cross-Cultural Psychology, 2026)
Humans instinctively adopt methods to reduce their risk of encountering harmful pathogens, yet their adherence to preventive health practices can often be erratic. Condoms exemplify one vital preventive tool against sexually transmitted infections (STIs) that, despite their effectiveness, are not consistently utilized. This pattern of behavior appears to persist even during periods of widespread disease transmission, with varied data from the COVID-19 pandemic indicating that condom usage remained inconsistent. The present study aimed to clarify these inconsistencies by examining changes in condom use cross-culturally. Heterosexual participants who were sexually active (N = 3,972 [1,327 men, 2,645 women], Mage = 22.82) across 18 countries were asked about their condom use prior to the pandemic, then about their current use. Results revealed a significant decline in Australia, Canada, Portugal, Vietnam, Uganda, and Taiwan. Vaccination percentage and lockdown stringency were associated with this decline cross-culturally. These findings continue to add concerns about the spread of STIs among young people during the pandemic.